2015
DOI: 10.1016/j.actatropica.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium falciparum histidine-rich protein 2 in the China–Myanmar border area

Abstract: Deletion of the Plasmodium falciparum histidine-rich protein 2 (pfhrp2) gene may affect the performance of PfHRP2-based rapid diagnostic tests (RDTs). Here we investigated the genetic diversity of the pfhrp2 gene in clinical parasite isolates collected in recent years from the China-Myanmar border area. Deletion of pfhrp2 has been identified in 4 out of 97 parasite isolates. Sequencing of the pfhrp2 exon 2 from 67 isolates revealed a high level of genetic diversity in pfhrp2, which is reflected in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
8
49
1
Order By: Relevance
“…Further, high prevalence of hrp2 deletion were observed compared to hrp3 deletion in all four regions. Similar predominant hrp2 deletion strains have been reported in previous studies from India [ 30 ] and Suriname [ 21 ], which are in contrast to other studies [ 17 19 , 47 , 38 40 , 48 , 49 ], where the frequency of hrp3 deletion was higher. Interestingly, high proportions of hrp2 deletion parasites were observed during summer, whereas the proportions of hrp2 deletion and hrp3 deletion parasites were nearly the same in peak season of malaria transmission (Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…Further, high prevalence of hrp2 deletion were observed compared to hrp3 deletion in all four regions. Similar predominant hrp2 deletion strains have been reported in previous studies from India [ 30 ] and Suriname [ 21 ], which are in contrast to other studies [ 17 19 , 47 , 38 40 , 48 , 49 ], where the frequency of hrp3 deletion was higher. Interestingly, high proportions of hrp2 deletion parasites were observed during summer, whereas the proportions of hrp2 deletion and hrp3 deletion parasites were nearly the same in peak season of malaria transmission (Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…South America was the first region to report the occurrence of false negative RDT results due to this gene deletion (Gamboa et al, 2010;Akinyi et al, 2013;Abdallah et al, 2015;Akinyi Okoth et al, 2015;Murillo Solano et al, 2015;Rachid Viana et al, 2017). Similar evidence was followed by more recent studies from Africa (Dolo et al, 2012;Wurtz et al, 2013;Parr et al, 2016;Beshir et al, 2017) and Asia (Kumar et al, 2013;Li et al, 2015;Bharti et al, 2016). Driven by the high impact of pfhrp2-detecting RDT use on malaria control, mathematical modelling exercises have identified low transmission regions of sub-Saharan Africa as the priority for pfhrp2-deletion investigations (Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
“…Of these, six studies were excluded from the analysis, because they did not evaluate pfhrp2 and pfhrp3 deletions in the field (Ramutton et al, 2012;Mendoza et al, 2013;Das et al, 2018;Parr et al, 2018) or referred to case studies (Houzé et al, 2011;Johora et al, 2017). Other six studies determined the combined genotypes of pfhrp2 and pfhrp3 status only on a subset of samples with negative RDT result (Kumar et al, 2013;Wurtz et al, 2013;Li et al, 2015;Bharti et al, 2016;Parr et al, 2016;Gupta et al, 2017). These studies were discarded from the analysis, because the respective data were intrinsically incomplete and biased by study design.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Phylogenetic analysis of the Ghana PfHRP2 revealed striking similarities with isolates from Kenya. In a study along the Chinese-Myanmar border, novel PfHRP2 repeat types arising from replacement of a single amino acid of eight amino acid repeats types were identified [33]. Nderu et al [18] also found 39 novel PfHRP2 repeat types.…”
Section: Discussionmentioning
confidence: 99%